The Role of Gravitation in Physics: Report from the 1957 Chapel Hill Conference - Cécile M. DeWitt (ed.) (Sources 5: Max Planck Research Library for the History and Development of Knowledge, 2011)
In January 1957, a group of physicists from several countries met at the University of North Carolina to discuss the role of gravitation in physics. The program was divided into two broad sections: unquantized and quantized general relativity. The first section included a review of classical relativity, its experimental tests, the initial value problem, gravitational radiation, equations of motion, and unified field theory. The second section included a discussion of the motivation for quantization, the problem of measurement, and the actual techniques for quantization. In both sections the relationship of general relativity to fundamental particles was discussed. In addition there was a session devoted to cosmological questions. A large part of the discussions is reproduced in the present report in an abridged form, followed by a conference summary statement by P. G. Bergmann. The Chapel Hill conference also marked the establishment of the Institute of Field Physics, directed by Bryce and Cécile DeWitt. The conference was the inaugural conference of this institute.